The Prevalence and Determinants of Vitamin D Inadequacy among U.S. Older Adults: National Health and Nutrition Examination Survey 2007-2014 - Orces, Carlos (Cureus, 2019)
Background Older adults (i.e., adults aged ≥ 60 years) are at higher risk of vitamin D deficiency compared to younger adults as a result of inadequate dietary vitamin D intake and limited exposure to sunlight. Thus, the present study aimed to describe the prevalence of vitamin deficiency and inadequacy among U.S. adults aged ≥ 60 years and the effect of vitamin D supplementation on 25, hydroxyvitamin D (25(OH)D) and its metabolites concentrations. Methods The present analysis was based on data from 6,261 participants in the National Health and Nutrition Examination Survey cycles 2007/2008 through 2013/2014. The prevalence of vitamin D deficiency and inadequacy was described according to demographic, behavioral, and health characteristics. Vitamin D deficiency was defined as 25(OH)D < 30 nmol/L; and vitamin D inadequacy was defined as < 50 nmol/L. Logistic regression models were assembled to examine the independent association of participants characteristics and the odds of having 25(OH)D inadequacy. Similarly, general linear models were used to assess the effect of vitamin D supplementation doses on 25(OH)D and its metabolites concentrations. Results The prevalence of 25(OH)D deficiency and inadequacy was 4.0% (standard error (SE), 0.4) and 17.4% (SE, 0.8), respectively. In general, the prevalence of 25(OH)D deficiency and inadequacy increased significantly among participants examined during the fall and winter months, women, non-Hispanic black patients, obese subjects, smokers, those physically inactive, and older adults with a daily vitamin D intake < 400 IU. After adjustment for potential confounders, subjects examined during the fall and winter months, females, non-Hispanic blacks, obesity, having a sedentary lifestyle, smokers, and a total vitamin D intake < 400 IU/day were variables significantly associated with increased odds of having vitamin D inadequacy. Notably, vitamin D supplement doses between 400 and 800 IU or > 800 IU/day were significantly correlated with higher 25(OH)D(3) concentrations considered as sufficient.  Conclusion 25(OH)D inadequacy remains prevalent among U.S. older adults. Notably, optimal 25(OH)D(3) concentrations were consistently seen among vitamin D supplement users. Despite this finding, nearly half of the participants did not take vitamin D supplements. Thus, vitamin D supplementation should be considered an effective strategy to maintain adequate 25(OH)D status among older adults.